Effect of Container Shape, Age, and Visual Acuity on the Readability of Prescription Label Information in Persons With Visual Impairments. (March 2022) - Connors, Elyse; Lee, Helen; Kim, Dae; Curtis, Amy; Freeland, Amy
Introduction: The readability of prescription drug labels has been found to be faster with labels attached to flat surfaces compared to round surfaces, in persons with visual impairment. This study extends this finding by examining the readability of drug labels, as measured by speed and accuracy, as they interact with factors of age and vision acuity across different container shapes.Methods: A repeated-measure, three-factor design (container shape, age, and vision acuity) with within-subject control was used with 54 adults with vision loss. Participants read 3 unique prescription drug labels across four container shapes, for a total of 12 trials. The amount of time needed to locate and read aloud 6 pieces of label information and the number of errors made in reading were outcome measures.Results: A two-way interaction was found between container shape and acuity for the time it takes to read the label information (Wald χ 2 = 22.836, df = 3, p < .001). The legally blind group required more time to read the label and had more variation in mean times across container type, compared to the low vision group. Both age and acuity showed statistically significant ( p < 0.001) main effects on reading accuracy.Discussion: Within the legally blind acuity group, cylinder-shaped containers took statistically significantly longer to read compared to the flat label by 18 seconds. Increased age and lower visual acuity negatively affected reading accuracy, across all container shapes.Implications for Practitioners: Individuals with legal blindness may need more time to read prescription drug labels and may benefit from labels adhered to flat surfaces over traditional cylindrical containers. As medication safety is a critical skill for independent living, practitioners should assess their clients' ability to access prescription drug label information, keeping in mind that these abilities may differ across different container shapes.